A new model for diagnostic fracture injection test (DFIT) complexity in unconventional reservoirs. (3rd May 2019) - Chen, Zhiming; Liao, Xinwei; Zhang, Jiali
Abstract: In the recent years, much attention has been paid to unconventional reservoirs of hydrogen and carbon which are good sources of hydrogen energy. To ensure sufficient energy organic, the first step is understanding the properties of those unconventional reservoirs. The diagnostic fracture injection test (DFIT) is a very good technique to estimate the parameters of the unconventional reservoirs. Unfortunately, most DFIT models do not involve the complex fracture networks caused by natural fractures, fissures, and microfractures. Highlights: To understand the properties of unconventional reservoirs of hydrogen and carbon. This paper introduces a generalized model with random fracture geometry. Complex fracture geometries can be generated by DFIT in shale reservoirs. Existing DFIT analysis so far have rarely considered complex fracture networks.